The Effect of Work Dicipline and Place to Employee Performance in PT. Pegadaian Cabang Manado Utara - Derek, Sheren Chelsea Natasya; Maringka, Tonny; Mantur, Mercy (Formosa Journal of Applied Sciences, 2024)
This study attempts to tryout the effects of discipline, workplace work on worker performance in pt.Pawnshops branches north manado.This research with quantitative technique, using the multiple linear regression.The final demonstrated that discipline work on this fact to effect positive and significant employee performance, so it is with the work on this fact able to exert a positive and significantly to worker performance and together work discipline and workplace able to exert a positive and significantly to worker performance in pt.Pawnshops branches north manado.Research is expected as a benchmark for employees in pt pawnshops branches manado north to the future can improve their performance at work.This finding might also be the base for further research in studying faktor-faktor way out of that will be able to support.